To Explore the Pathogenesis of Vascular Lesion of Type 2 Diabetes Mellitus Based on the PI3K/Akt Signaling Pathway - Jia-Rong Gao; Xiu-Juan Qin; Zhao-Hui Fang; Li-Shan; Li-Ping Han; Hui-Jiang; Ming-Fei Guo; Nan-Nan Jiang (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (T2DM) has become a chronic disease, serious harm to human health. Complications of the blood pipe are the main cause of disability and death in diabetic patients, including vascular lesions that directly affects the prognosis of patients with diabetes and survival. This study was to determine the influence of high glucose and related mechanism of vascular lesion of type 2 diabetes mellitus pathogenesis. Methods. In vivo aorta abdominalis of GK rats was observed with blood pressure, heart rate, hematoxylin and eosin (H&E), Masson, and Verhoeff staining. In vitro cells were cultured with 30 mM glucose for 24 h. RT-QPCR was used to detect the mRNA expression of endothelial markers PTEN, PI3K, Akt, and VEGF. Immunofluorescence staining was used to detect the expression of PTEN, PI3K, Akt, and VEGF. PI3K and Akt phosphorylation levels were detected by Western blot analysis. Results. Heart rate, systolic blood pressure, diastolic blood pressure, and mean blood pressure in the GK control group were higher compared with the Wistar control group and no difference compared with the GK experimental model group. Fluorescence intensity of VEGF, Akt, and PI3K in the high-sugar stimulus group was stronger than the control group; PTEN in the high-sugar stimulus group was weakening than the control group. VEGF, Akt, and PI3K mRNA in the high-sugar stimulus group were higher than the control group; protein expressions of VEGF, Akt, and PI3K in the high-sugar stimulus group were higher than the control group. PTEN mRNA in the high-sugar stimulus group was lower than the control group. Protein expression of PTEN in the high-sugar stimulus group was lower than the control group. Conclusions. Angiogenesis is an important pathogenesis of T2DM vascular disease, and PTEN plays a negative regulatory role in the development of new blood vessels and can inhibit the PI3K/Akt signaling pathway.